SOCIOLINGUISTICS PERSPECTIVE ON ACRONYMS FORM IN BAHASA INDONESIA - Syafrina Prihatini; Susy Deliani; Muhammad Haekal Harahap (FKIP Universitas Al Washliyah Medan, 2022)
The background of this research deals with two problems, firstly language as an instrument of communication which is used by society and secondly the society as users and speakers of language as well as changes on vocabulary or acronyms. This research focused on the process of acronym formation in the Sociolinguistics perspective. Events in society are reflected in language, in this study the formation of acronyms. This study is a descriptive qualitative study, where social phenomena are described by their characteristics. The data were collected by observing and recording the acronym found. The source of this research data is Refly Harun's program on YouTube with the title